2020
DOI: 10.24875/bmhim.20000101
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus gallolyticus subsp. pasteurianus: un agente inusual ocasionando una infección común

Abstract: Boletín Médico del Hospital Infantil de México CASO CLÍNICO ResumenIntroducción: Streptococcus gallolyticus subsp. pasteurianus es un coco grampositivo, catalasa negativo, perteneciente al grupo D de Lancefield, que se encuentra relacionado con cuadros de sepsis neonatal, específicamente con meningitis. Caso clínico: Se reporta el caso de un paciente de 2 meses con un cuadro de meningitis por S. gallolyticus subsp. pasteurianus. Se describen la sintomatología y el abordaje diagnóstico y terapéutico. Asimismo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…The number of patients included in each study ranged from 1 to 23 patients (Table, Supplemental Digital Content 1, http://links.lww.com/INF/F527). 5–8,12–53 Most of the included studies showed an overall good quality (Tables, Supplemental Digital Content 2, http://links.lww.com/INF/F528 and Supplemental Digital Content 3, http://links.lww.com/INF/F529). The main weaknesses included retrospective design and small sample size.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The number of patients included in each study ranged from 1 to 23 patients (Table, Supplemental Digital Content 1, http://links.lww.com/INF/F527). 5–8,12–53 Most of the included studies showed an overall good quality (Tables, Supplemental Digital Content 2, http://links.lww.com/INF/F528 and Supplemental Digital Content 3, http://links.lww.com/INF/F529). The main weaknesses included retrospective design and small sample size.…”
Section: Resultsmentioning
confidence: 97%
“…The studies included 34 case reports, 9 case series and 3 letters to the editor. There were 41 articles in English and 5 in other languages (3 Spanish, 12–14 1 French 15 and 1 Japanese 16 ). Majority (61%) of studies reviewed were from Asia, predominantly from Japan, Taiwan, Thailand and Singapore.…”
Section: Resultsmentioning
confidence: 99%